Mainstreaming genetics into Italian prenatal care: exploring the future implementation of non-invasive prenatal testing (NIPT) in the Italian National Healthcare System using stakeholder interviews - Giulia Sesa; Katarzyna Czabanowska; Kristiaan Kok; Terry Vrijenhoek (BMJ Publishing Group, 2024)
Introduction Non-invasive prenatal testing (NIPT) has revolutionised the way prenatal testing is performed globally. Italy is one of the European countries considering incorporating NIPT nationwide into the publicly funded healthcare system. Given the extensive autonomy granted to the private sector, that not all technological applications result in equal benefits, and that only a few Italian regions currently offer NIPT through the public healthcare system free of charge, it is crucial to consider how to implement such a technology in the Italian public healthcare sector.Methods A qualitative study consisting of 12 semistructured interviews was performed. The study population included gynaecologists, geneticists, bioethicists, health economists and public health professionals. Non-probability sampling techniques were used to recruit the study's participants. Content analysis was employed to analyse the data.Results From the interviews, it emerged that a contingent implementation of NIPT for major chromosomal aneuploidies screening seems the most cost-effective and logical in the Italian context. No consensus was reached on fetal sex and sex chromosome aneuploidies screening. Most interviewees disagreed with making whole-genome/whole-exome sequencing available through the public sector. The high appreciation of NIPT, its potential to advance fundamental objectives of healthcare systems and its compatibility with the Italian prenatal testing culture are among the factors that may facilitate the transition of NIPT from the private to the public sector. Mainstreaming NIPT in the public healthcare system is challenged by its high costs, current offer, lack of prioritisation and regional differences.Conclusions While transitions take time and are challenging to achieve, this study shows that the current prenatal testing structure and practice would only need modest adjustments to accommodate NIPT, offering hope for the future. Future studies could expand this research by involving a broad range of stakeholders and investigating the effects of various NIPT implementation strategies presently employed across Italian regions.